2016
DOI: 10.5792/ksrr.2016.28.3.239
|View full text |Cite
|
Sign up to set email alerts
|

Use of a New Knee Prosthesis as an Articulating Spacer in Two-Stage Revision of Infected Total Knee Arthroplasty

Abstract: PurposeTo report our experience with two-stage revision using a new femoral component (NFC) spacer (Depuy Synthes) as an articulating spacer.Materials and MethodsIn this retrospective study, we reviewed 22 two-stage revisions that were performed using an NFC spacer in 22 patients suspected of having an infected total knee arthroplasty (TKA) from December 2010 to March 2013. The result was considered successful when eradication of infection was achieved using only one NFC spacer.ResultsThe average time from pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Treatment options are antibiotic pressure, debridement, single-or double-stage revision, arthrodesis, resection arthroplasty, and amputation. Revision surgery also has single-stage or double-stage revision options [134][135][136].…”
Section: Treatmentmentioning
confidence: 99%
“…Treatment options are antibiotic pressure, debridement, single-or double-stage revision, arthrodesis, resection arthroplasty, and amputation. Revision surgery also has single-stage or double-stage revision options [134][135][136].…”
Section: Treatmentmentioning
confidence: 99%
“…The use of autoclaved TKA components as temporary spacers was first described by Scott et al [42], and has demonstrated modest popularity with recurrence rates of between 0 and 21% [1, 4, 6, 8, 10–13, 15, 18, 21, 24, 25, 32, 37, 39]. In an effort to obviate the risk of recurrent infection arising from incomplete sterilization, and taking into account the possibility of indefinitely retained spacers, new TKA implants were introduced [3, 17, 18, 29, 43].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of chronic infection after TKA, a two-stage revision arthroplasty has been recommended as a treatment. [4][5][6][7] In the first stage of revision, the femoral component removed from the patient is reused after autoclaving and applying an antibiotic-impregnated cement spacer. Proper antimicrobial treatment must be followed until the second stage of revision is performed.…”
Section: Introductionmentioning
confidence: 99%